2020
DOI: 10.1111/jce.14660
|View full text |Cite
|
Sign up to set email alerts
|

A novel open‐source software‐based high‐precision workflow for target definition in cardiac radioablation

Abstract: Introduction: Noninvasive ablative radiotherapy of cardiac arrhythmias (stereotactic ablative body radiation) has shown promising initial results. Precise targeting of the arrhythmogenic substrate is paramount to limit adverse effects to healthy myocardium, organs at risk, and cardiac implantable electronic devices. Using electroanatomic maps for treatment planning is technically challenging. Methods and Results: Using the free open-source 3D Slicer software platform we established a workflow for high-precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Fortunately, many authors decided to challenge this problem. For example, in May and July of 2020, Brett et al [ 38 ] and Hohmann et al [ 39 ] published workflow descriptions on converting catheter-based EP maps to DICOM. The software developed by Hohmann et al supports CARTO 3 (Biosense Webster), EnSite Velocity/Precision (Abbott), and RHYTMIA HDx (Boston Scientific) cardiac mapping systems.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, many authors decided to challenge this problem. For example, in May and July of 2020, Brett et al [ 38 ] and Hohmann et al [ 39 ] published workflow descriptions on converting catheter-based EP maps to DICOM. The software developed by Hohmann et al supports CARTO 3 (Biosense Webster), EnSite Velocity/Precision (Abbott), and RHYTMIA HDx (Boston Scientific) cardiac mapping systems.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to rely on an experienced cardiologist to determine the origin of the VT based on EAM against the reference anatomy and to delineate it on CCTA images as the GTV, for which a respiratory movement range can be generated on r4DCT images. Several studies have reported the registration and fusion workflow of EAM and CT images, providing an objective reference for cardiologists (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…In this series, and reflecting current worldwide experience and literature, we used a range of approaches from manual delineation methods to more sophisticated computer-assisted visualisation methods still under development. [26][27][28] The optimum dose and delivery platform for cardiac SABR is yet to be established. We used a single fraction 25 Gy regime as reported by all groups previously.…”
Section: Discussionmentioning
confidence: 99%